Very advanced maternal age. (21st December 2020) - Howell, Alice; Blott, Margaret
Abstract : Key content: Increasing fertility options have led to increased birth rates among women over the age of 45 years. Most women aged 45 years or older conceive via assisted reproductive technologies, which are associated with increased risks to both mother and fetus. Multiple pregnancies are disproportionately common in this group of women as a result of multiple embryo transfer. The maternal and fetal risks are increased significantly in multiple pregnancies. A maternal age of 45 years or more is associated with complications in early pregnancy and the antenatal period and with significant obstetric complications. Fetal complications are increased in this group; in particular there is an increased risk of multiple births, increased rates of preterm birth and higher perinatal mortality rates. Learning objectives: To understand the maternal implications, complications and risks of pregnancy in women of very advanced maternal age, to aid counselling this group of women prior to and during pregnancy. To understand the fetal complications associated with pregnancy in women of very advanced maternal age, including stillbirth and preterm labour. To establish an evidence‐based approach to the antenatal management and care of women of very advanced maternal age.